Psychological peculiarities of mental activity formation in students (Actual Problems of Psychology in Educational Institutions, 2018)
The article is devoted to the problem of the formation of mentalactivities in student age The essence of the definition of "mentalactions" in the article is presented domestic psychology. An attempt ismade to determine the polarity structures of mental actions. It emphasizes therole of mental activity in the process assimilation of educational material. Thedynamics and main types are determined mental actions in the course ofcomprehension of scientific information. Specifics are revealed the functioningof mental activities in the conditions of studying at universities. Presented theresults of the empirical study of the level of development of mental activity instudents
Keywords: learning, teaching, comprehension, mental actions, logical mediation, semantic structures, analytical and synthetic activity, generalization